2017
DOI: 10.15171/jlms.2017.s12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Different Laser Activated Bleaching Methods on Enamel Susceptibility to Caries; An In Vitro Mode

Abstract: IntroductionIn recent years, tooth whitening has become one of the most growing oral care sectors, boosted by patients, demanding both healthy mouth and attractive smile.1 As tooth color relies on the composition of tooth tissues, any chemical, mechanical or biological change can damage the esthetic equilibrium of the smile.2 Bleaching is a simple, non-restorative and noninvasive treatment for discolored teeth that is capable of satisfaction of the high demanding patients. So it has attracted much interest fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…One study evaluated the effect of 35% hydrogen peroxide activated by LED, halogen light, and diode laser, and found a significant reduction in micro-hardness and variations in morph ology [28]. In the research of Ashnagar et al, conventional bleaching with 40% hydrogen peroxide gel alone and activation with a diode laser or Nd:YAG laser showed a reduction in Knoop hardness [5]. Kabbach et al observed a significant reduction in micro-hardness in the light-activated bleaching group [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study evaluated the effect of 35% hydrogen peroxide activated by LED, halogen light, and diode laser, and found a significant reduction in micro-hardness and variations in morph ology [28]. In the research of Ashnagar et al, conventional bleaching with 40% hydrogen peroxide gel alone and activation with a diode laser or Nd:YAG laser showed a reduction in Knoop hardness [5]. Kabbach et al observed a significant reduction in micro-hardness in the light-activated bleaching group [39].…”
Section: Discussionmentioning
confidence: 99%
“…These particles target the colored tooth molecules and convert them into smaller and less colored molecules [1][2][3]. Although some researchers have reported no adverse effects after bleaching, others have claimed that the use of such products can cause such effects, including changes to the enamel and dentin surfaces, the reduction of surface and subsurface micro-hardness, the reduction of Ca and p ratios, the loss of organic components from the tooth surface, and dental hypersensitivity [4,5]. During bleaching treatment, the morphological structure of the enamel surface is affected and its prisms are destroyed [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ashnagar et al 23 reported a decrease in Knoop microhardness after bleaching with the conventional technique with 40% hydrogen peroxide gel alone or with diode or Nd:YAG laser beams. In contrast to the present study, Ahmed et al 24 did not report any deleterious effects on enamel microhardness after the activation of bleaching agents with different light sources.…”
Section: Discussionmentioning
confidence: 99%
“…Light, heat, or laser can be used to accelerate the oxidation-reduction reaction and activation of the chemical agents involved in the bleaching process [12]. Various lasers such as Nd:YAG laser (1064 nm), diode laser (810 and 980 nm), Potassium-Titanyl-Phosphate laser (KTP, 532 nm), and Erbium: Yttrium Aluminum Garnet laser (Er: YAG, 2940 nm) have been used to accelerate bleaching gel [13][14][15][16][17]. By reviewing the papers published in this area, no study was done before on the effect of the laser immediately after the office-bleaching process on recovering the shear bond strength of the orthodontic brackets.…”
Section: Introductionmentioning
confidence: 99%